Photodynamic inactivation mediated by erythrosine and its derivaties on foodborne pathogens and spoilage bacteria - Yassunaka, Natália Norika (2015)
: The purpose of the present study was to evaluate the efficacy of photodynamic inactivation (PDI) mediated by erythosine (ERY) and its ester derivatives erythrosine methyl ester (ERYMET) and erythrosine butyl ester (ERYBUT) on foodborne pathogens and spoilage bacteria. We evaluated Staphylococcus aureus ATCC 25923, Aeromonas hydrophila ATCC 7966, Salmonella enterica serotype Typhimurium ATCC 14028, Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853. The toxicity of all of the compounds was assessed in VERO cells. Photodynamic inactivation mediated by ERY and its derivatives combined with a light-emitting diode (LED) was performed at different concentrations and exposure times. S. aureus was more photosensitive than Gram-negative bacteria to ERY, ERYMET, and ERYBUT. The ERY-mediated PDI of S. aureus induced a significant reduction of 4.0 log CFU/ml at a light dose of 40 J/cm2. ERYMET and ERYBUT at lower light doses than ERY completely eradicated S. aureus. When photoirradiated with ERY at light doses of 156 and 234 J/cm², A. hydrophila was completely eradicated. ERYBUT was more efficient in the PDI of A. hydrophila than ERYMET, even at 1 x 10-5 M and lower light doses. S. Typhimurium, E. coli, and P. aeruginosa required higher concentrations of photosensitizers to reduce cell survival. ERYBUT and ERY may be promising photosensitizing agents against A. hydrophila and S. aureus. They were effective at reducing bacterial counts at non-toxic concentrations. The photoinactivation rate of the evaluated bacteria decreased in the following order: S. aureus > A. hydrophila > E. coli > S. Typhimurium > P. aeruginosa.